Influenza virus M2 targets cystic fibrosis transmembrane conductance regulator for lysosomal degradation during viral infection. Issue 7 (20th March 2015) - Londino, James David; Lazrak, Ahmed; Noah, James W.; Aggarwal, Saurabh; Bali, Vedrana; Woodworth, Bradford A.; Bebok, Zsuzsanna; Matalon, Sadis
ABSTRACT: We sought to determine the mechanisms by which influenza infection of human epithelial cells decreases cystic fibrosis transmembrane conductance regulator (CFTR) expression and function. We infected human bronchial epithelial (NHBE) cells and murine nasal epithelial (MNE) cells with various strains of influenza A virus. Influenza infection significantly reduced CFTR short circuit currents ( I sc ) and protein levels at 8 hours postinfection. We then infected CFTR expressing human embryonic kidney (HEK)‐293 cells (HEK‐293 CFTRwt) with influenza virus encoding a green fluorescent protein (GFP) tag and performed whole‐cell and cell‐attached patch clamp recordings. Forskolin‐stimulated, GlyH‐101‐sensitive CFTR conductances, and CFTR open probabilities were reduced by 80% in GFP‐positive cells; Western blots also showed significant reduction in total and plasma membrane CFTR levels. Knockdown of the influenza matrix protein 2 (M2) with siRNA, or inhibition of its activity by amantadine, prevented the decrease in CFTR expression and function. Lysosome inhibition (bafilomycin‐A1), but not proteasome inhibition (lactacystin), prevented the reduction in CFTR levels. Western blots of immunoprecipitated CFTR from influenza‐infected cells, treated with BafA1, and probed with antibodies against lysine 63‐linked (K‐63) or lysine 48‐linked (K‐48) polyubiquitin chains supported lysosomal targeting. These results highlight CFTR damage, leading to early degradation as an important contributing factor to influenza infection‐associated ion transport defects.—Londino, J. D., Lazrak, A., Noah, J. W., Aggarwal, S., Bali, V., Woodworth, B. A., Bebok, Z., Matalon, S. Influenza virus M2 targets cystic fibrosis transmembrane conductance regulator for lysosomal degradation during viral infection. FASEB J . 29, 2712–2725 (2015). www.fasebj.org